Floristic geography of woody plants in the big plot of Gulinqing karst forest in Yunnan Province - LIU Qun1,2, CHEN Wenhong1, HUANG Hong1,3, YANG Chong1, FAN Changli1, ZHANG Jinguo4, SHUI Yumin1* (Guangxi Zhiwu)
Based on the 25 hm2 karst forest big plot in Gulinqing, Yunnan, we carried out sample-plot investigation, specimen collection and identification, floristic analysis, Jaccard similarity coefficient and principal component analysis(PCA), in order to explore its floristic characteristics and the status of the Gulinqing big plot in Yunnan and the geographical relationships among Gulinqing in Yunnan, Bubeng in Yunnan, and Nonggang in Guangxi, China. The results were as follows:(1)There were about 78 families, 238 genera, and 406 species(including infraspecies taxa and excluding woody vines)of woody plants with DBH≥1 cm.(2)In the plot, the families with 2-5 species and with one species were dominant and accounted for 37.18% and 34.62% of the total number of families, respectively, while the genera with 2-4 species and with one species were also dominant and accounted for 30.25% and 65.13% of the total number of genera, respectively.(3)Through analysis of the areal-types of families and genera, it was found that it had been divided into 9 areal-types and 7 variations at the family level, and the proportion of families was the highest at Pantropic, accounting for 50.77%, and the ratio of tropical flora to temperate flora(R/T)was 4.42; there were 11 areal-types at the genera level, mainly composed of Tropical Asian, Pantropic, Old World Tropics, accounting for 33.47%, 18.22%, and 13.98%, respectively, and R/T of the genera was 10.25.(4)The composition of Gulinqing, Bubeng and Nonggang big plots showed that Gulinqing and Bubeng had the highest similarity in family and genera level at Jaccard similarity coefficient(0.674 and 0.395, respectively), and Bubeng and Nonggang with the smallest Jaccard similarity coefficient(0.575 and 0.297, respectively).(5)The analysis results of the floristic spectrum PCA and the Jaccard similarity coefficient in the level of genera were similar, but different one at the level of families, e.g. a higher geographical connection between Gulinqing and Nonggang through the PCA analysis of family. In summary, this plot has a high diversity of families and genera, significant tropical characteristics, ancient floristic characteristics, obvious transitional status and extensive flora connections. However, there is an inconsistent geographical connection among Gulinqing, Bubeng and Nonggang from the composition and floristic spectrum.